Effects of blended microbial feed additives on performance, meat quality, gut microbiota and metabolism of broilers - Zhou, Luli; Li, Hui; Hou, Guanyu; Hu, Chengjun; Ji, Fengjie; Peng, Weiqi; Zhou, Hanlin; Wang, Dingfa (Frontiers in Nutrition, 2022)
This study aimed to investigate the effects of blend microbial feed additive (BMFA) on meat quality, gut microbiota and metabolism of broilers. A total of 240 seventy-day-old female Wenchang broilers were randomly allocated into four groups with five replicates of 12 broilers each. Broilers in the control group was fed a basal diet (S0), and the other three groups were fed the same basal diet supplemented with 0.2% (S1), 0.4% (S2), or 0.6% (S3) of BMFA for 54 days, respectively. The results showed that broilers in S2 and S3 had lower average daily feed intake (ADFI) compared with S0 and S1 (P < 0.05). However, diet supplementation with BMFA had no significantly influence on the average daily gain (ADG) and the ratio of ADFI to ADG (F/G) (P > 0.05). The highest thigh muscle percentage was observed in S2 (P < 0.05). Diet supplementation with BMFA reduced the shear force in both breast and thigh muscle (P < 0.05) of broilers. An increase (P < 0.05) in the total unsaturated fatty acid (USFA), monounsaturated fatty acids (MUFA), and ratio of unsaturated fatty acids to saturated fatty acid (USFA/SFA) in breast muscles was observed in S3 compared with S0. It was found that the S3 had a relatively higher abundance of Lactobacillus (P < 0.001), as well as a lower abundance of the Bacteroides, Rikenellaceae RC9 gut group, Olsenella, Prevotellaceae UCG-001 and Prevotella (P < 0.05) than that in the S0. Correlation analysis indicated that a total of 17 differential metabolites between the S3 and S0 were significantly correlated with the 7 differential genera microflora. Overall, diet supplementation with 0.6% of BMFA can significantly improve the meat quality of broilers by decreasing the level of SFA and enhancing the levels of the total USFA, MUFA and USFA/SFA ratio in breast muscles. Those findings were tightly bound to the higher proportion of Lactobacillus genus in the intestinal tract of broilers influenced by BMFA.